Reorganization of Extracellular Matrix in Placentas from Women with Asymptomatic Chagas Disease: Mechanism of Parasite Invasion or Local Placental Defense? - Juan Duaso; Erika Yanez; Christian Castillo; Norbel Galanti; Gonzalo Cabrera; Gabriela Corral; Juan Diego Maya; Inés Zulantay; Werner Apt; Ulrike Kemmerling (Journal of Tropical Medicine)
Chagas disease, produced by the protozoan Trypanosoma cruzi (T. cruzi), is one of the most frequent endemic diseases in Latin America. In spite the fact that in the past few years T. cruzi congenital transmission has become of epidemiological importance, studies about this mechanism of infection are scarce. In order to explore some morphological aspects of this infection in the placenta, we analyzed placentas from T. cruzi-infected mothers by immunohistochemical and histochemical methods. Infection in mothers, newborns, and placentas was confirmed by PCR and by immunofluorescence in the placenta. T. cruzi-infected placentas present destruction of the syncytiotrophoblast and villous stroma, selective disorganization of the basal lamina, and disorganization of collagen I in villous stroma. Our results suggest that the parasite induces reorganization of this tissue component and in this way may regulate both inflammatory and immune responses in the host. Changes in the ECM of placental tissues, together with the immunological status of mother and fetus, and parasite load may determine the probability of congenital transmission of T. cruzi.